Handbook of brewing - Priest, Fergus G.; Stewart, Graham G. (Food science and technology, 2006)
It has been ten years since its first edition, making the Handbook of Brewing, Second Edition the must have resource on the science and technology of beer production. It recounts how during this time, the industry has transformed both commercially and technically and how many companies have been subsumed into large multinationals while at the other extreme, microbreweries have flourished in many parts of the world. It also explains how massive improvements in computer power and automation have modernized the brewhouse while developments in biotechnology have steadily improved brewing efficiency, beer quality, and shelf life. In addition to these topics, the book, written by an international team of experts recognized for their contributions to brewing science and technology, also covers traditional beer styles as well as more obscure beverages such as chocolate- or coffee-flavored beers. It includes the many factors to be considered in setting up and operating a microbrewery as well as the range of novel beers and beer-related products currently being considered by the brewing industry. It also describes new avenues that challenge the brewer’s art of manufacturing a quality beverage from barley-based raw materials. Thorough and accessible, the Handbook of Brewing, Second Edition provides the essential information for those who are involved or interested in the brewing industry.